CxNy: New Carbon Nitride Organic Photocatalysts - López-Salas, Nieves; Albero, Josep (Frontiers in Materials, 2021)
The search of metal-free and visible light-responsive materials for photocatalytic applications has attracted the interest of not only academics, but also the industry in the last decades. Since graphitic carbon nitride (g-C3N4) was first reported as metal-free photocatalyst, this has been widely investigated in different light-driven reactions. However, the high recombination rate, low electrical conductivity and lack of photoresponse in most of the visible range has elicited the seek of alternatives. In this regard, a broad family of carbon nitrides (CxNy) materials was anticipated several decades ago. However, the researchers’ attention in these materials has just wake up in the last years due to the recent success in the syntheses of some of these materials (i.e. C3N3, C2N, C3N and C3N5, among others), together with theoretical simulations pointing at the materials excellent physico-chemical properties (i.e. crystalline structure and chemical morphology, electronic configuration and semiconducting nature, or high refractive index and hardness, among others) and optoelectronic applications. The performance of CxNy, beyond C3N4, has been barely evaluated in real applications including energy conversion, storage and adsorption technologies, and further work must be carried out, especially experimentally, in order to confirm the high expectations raised by simulations and theoretical calculations. Herein, we have summarized the scarce literature related to recent results reporting synthetic routes, structures and the performance of these materials as photocatalysts. Moreover, the challenges and perspectives at the forefront of this field using CxNy materials are disclosed. We aim to stimulate the research of this new generation of CxNy -based photocatalysts, beyond C3N4, with improved photocatalytic efficiencies by harnessing the striking structural, electronic, and optical properties of this new family of materials.